(4y + 5)(2y + 5)
Factor by grouping:
8y^2 + 30y +25
= 8y^2 + 10y + 20y + 25
= 2y(4y + 5) + 5(4y + 5)
= (4y + 5)(2y + 5)
2007-05-23 13:12:22
·
answer #1
·
answered by Anonymous
·
3⤊
0⤋
(4y + 5) * (2y + 5)
Just use the quadratic formula to find notional y values:
y = -1¼ and -2½
Now rearrange so it is 0 on the right:
y + 1¼ = 0 and y + 2½ = 0
Now you have the basic factors: (y + 1¼) * (y + 2½) but they not only look aggravating, but do not yet yield the original polynomial. Let's rid ourselves of the fractions by multiplying the first one by 4 on each side and the second by two on each side:
(y + 1¼) * 4 = 0 * 4 and (y + 2½) * 4 = 0 *4
(4y + 5) = 0 and (2y + 5) = 0
Let's put it in factor form again and see if any further adjustments are required to have factors that yield the original polynomial:
(4y + 5) * (2y + 5)
Yep, we're done.
2007-05-23 20:52:03
·
answer #2
·
answered by Mike T 2
·
0⤊
0⤋
8y^2+30y+25
=8y^2+10y+20y+25
=2y(4y+5)+5(4y+5)
=(4y+5)(2y+5)
2007-05-23 20:19:15
·
answer #3
·
answered by alpha 7
·
0⤊
0⤋
(4y+5) (2y+5)
2007-05-23 20:14:38
·
answer #4
·
answered by mimi 3
·
1⤊
0⤋
(4y+5) (2y+5)
2007-05-23 20:12:27
·
answer #5
·
answered by marian 2
·
1⤊
0⤋
y = (-30 +/- sqrt(900-800))/16
y = (-30 +/- sqrt(100))/16
y = (-30 +/- 10)/16
y = -40/16 or y = -20/16
y = -2.5 or y = -1.25
2007-05-23 20:14:50
·
answer #6
·
answered by TychaBrahe 7
·
0⤊
2⤋